ANALISIS PENGGUNAAN SISTEM APLIKASI e-PNBP TERHADAP PENGELOLAAN PNBP DI DIREKTORAT JENDERAL MINERAL DAN BATUBARA KEMENTERIAN ESDM - Rio Eka Putra; Murad Murad; Fadhillah Fadhillah (Journals Mining Engineering : Bina Tambang, 2021)
Abstarct. Increasing the optimization of state revenue is still a challenge for the Directorate General of Mineral and Coal in managing PNBP. Since the transfer of mining supervision to the central government, the challenges have become bigger and increase. Various efforts have been made by the Directorate General of Mineral and Coal but based on the Audit Results Report (LHP) BPK RI there are still various findings related to PNBP management, including the value that must be paid is not in accordance with the obligations that must be deposited, late payments, and the implementation of regulations and regulations that are not yet optimal. To solve this problem, the Directorate General of Mineral and Coal has built an e-PNBP Application System which aims to simplify the calculation of PNBP obligations by the payer, facilitate the evaluation and verification of PNBP obligations by evaluators, and to make payment billing. To find out the performance of the system, it is necessary to conduct testing by interviewing and observing the evaluators who use it, calculating the compulsory payment assessment index and conducting the Mann Whiteney test on state revenue data as a product of the system.Keyword: PNBP Ditjen Minerba, Permasalahan PNBP, Pengelolaan PNBP, Sistem Aplikasi e-PNBP, Uji Mann Whiteney